Simulation and analysis of inbound baggage handling at Keflavík Airport - Kristinn Ingi Guðjónsson 1993- (2023)
Improving customer satisfaction is always the goal for every airport and airline, and the last place to disappoint is the handling of the baggage. Therefore baggage handling is an essential part of the passenger experience. Baggage handling can be split into outbound baggage handling and inbound baggage handling. Outbound baggage handling is when passengers are departing and the baggage is screened for prohibited substances, sorted and placed into the airplane. Inbound baggage handling is the process of delivering the baggage from the plane to the arrival passengers. In this thesis, an analysis of the inbound baggage process was examined. A simulation model was built that concentrated on the inbound baggage handling process at Keflavík Airport. The simulation model replicates the Baggage Claim area and helps identify the system’s bottlenecks or possible problem that can aid decision-making for the operations department of the airport. Various scenarios were made to determine the delimitation of the system. The simulation model explored how the system reacted with different scenarios and when the system needed external help because of system overload. Results from the model indicated that the system could handle the day to day operations but that it was sensitive during peak times. The model showed how important it is for the operations department of the airport to have a well planned schedule for the flights and be able to be proactive when handling unpredictable scenarios by using i.e the simulation model. Að auka ánægju viðskiptavina er alltaf markmið allra flugvalla og flugfélaga og síðasti staðurinn til að valda vonbrigðum er meðhöndlun á farangri. Ferill farangursins og hvernig hann er meðhöndlaður er því ómissandi hluti af upplifun farþega. Hægt er að skipta farangurs ferlinum á tvo vegu, ferill farangurs á útleið og ferill heimkomu farangurs. Ferill farangurs á útleið byrjar þegar brottfarar farþegi kemur með farangur á á flugvöllinn, farangurinn er skimaður fyrir ólöglegum efnum, flokkaður og settur ...